Japanese spotted fever in an area endemic to SFTS virus: Case report and review of the literature - Liu, Su-nan; Li, Wei (Medicine (Baltimore), 2024)
Rationale: The geographic spread of Japanese spotted fever (JSF) in China is gradually expanding, particularly in regions where severe fever with thrombocytopenia syndrome (SFTS) is highly prevalent, with both diseases sharing similarities in epidemiology and clinical presentation. The microbiological diagnosis of JSF is challenging, compounded by low awareness among healthcare professionals in newly affected areas. Moreover, primary healthcare facilities without polymerase chain reaction (PCR) testing capabilities for SFTS often misdiagnose JSF as SFTS. Patient concerns: All 3 patients had a history of working in the fields, with cold like symptoms in the early fever stages, but the fever did not improve after a few days. The accompanying symptoms were also very different. Physical examination revealed enlarged lymph nodes, different forms of rash, with or without eschar. Laboratory tests showed thrombocytopenia, eosinophilia, elevated lactate dehydrogenase, and transaminase, with 1 patient experiencing renal damage. It is worth noting that these 3 patients reside in an area where SFTS is endemic, and there have been no prior reports of JSF. They exhibited clinical symptoms and laboratory test results closely resembling those of SFTS. Therefore, they were initially misdiagnosed with SFTS in their local hospitals. Diagnoses: The 3 patients who arrived at our hospital 7 days after symptom onset and were subsequently diagnosed with JSF by metagenomic next-generation sequencing (mNGS). Interventions: Doxycycline treatment for 1 week. Outcomes: The patients' symptoms quickly improved with no side effects, and the results of laboratory tests went back to normal. Lessons: By comparing the clinical characteristics of JSF patients and SFTS patients comprehensively, we found that APTT and procalcitonin levels may be valuable in assisting in the identification of SFTS and JSF. In all areas where tick-borne diseases are endemic, include SFTS-epidemic areas, we recommend using the Weil-Felix test to screen for potential rickettsiosis in patients presenting with fever and thrombocytopenia with or without rash in primary healthcare settings, as well as simultaneous testing for the SFTS virus and spotted fever group rickettsioses sequence. Additionally, mNGS sequencing should be used to confirm the diagnosis and provide information for epidemiological investigations in patients who are suspected of having spotted fever group rickettsiosis.